Preform design in forging process of complex parts by using quasi-equipotential field and response surface methods. Issue 1 (July 2015) - Guan, Yanjin; Bai, Xue; Liu, Mujuan; Song, Libin; Zhao, Guoqun
Abstract The preform design is the key to bulk metal forming. An approach to optimize 3D preform shape in multi-step die forging based on quasi-equipotential field method and response surface method is employed. Firstly, optimum preforging shape is determined by means of quasi-equipotential field method and response surface optimization. Secondly, longitudinal and cross-section curve methods are introduced to design advisable blocking blank based on the optimized preforging shape. Using the method, the optimized preforging shape is determined in the hot forging of the pendulum mass. Based on the optimized preforging shape, the advisable blocking blank is constructed. The final preform design, including the advisable blocking blank and preforging shape, is completed. The desired pendulum mass forging without any defects and with smaller flash is obtained.